Persepsi Guru PAUD Terhadap Penggunaan Teknologi Pembelajaran Berbasis Artificial Intelligence (AI) Untuk Anak Usia Dini - Riana, Linda Wulan; Amalia, Siska; Annisa, Nasywa Nur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study AIms to explore the perceptions of early childhood education (PAUD) teachers in Kutai Kartanegara regarding the use of artificial intelligence (AI)-based learning technology. Using a descriptive qualitative approach, the research gathered data through in-depth interviews and participatory observations. The findings show that PAUD teachers in Kutai Kartanegara have a positive view of the use of AI technology, especially in supporting more personalized, adaptive, and interactive learning. Several AI applications, such as adaptive learning platforms (e.g., Khan Academy Kids, ABC Mouse) and virtual assistants (e.g., Google Assistant, Alexa), have proven to offer significant benefits in enhancing children's engagement and learning experiences. However, key challenges include limited technological infrastructure, teachers' technical skills, and financial resources. Despite these challenges, most teachers express a positive attitude towards AI and are willing to adopt it if provided with adequate training and support. This study suggests the need for collaboration between the government, educational institutions, and the community to provide training and technological facilities to ensure the effective implementation of AI in early childhood education. Thus, AI is expected to enrich children's learning experiences without overlooking their social and emotional needs